Genetic and morphological support for possible sympatric origin of fish from subterranean habitats - Hashemzadeh Segherloo, Iraj; Normandeau, Eric; Benestan, Laura; Rougeux, Clément; Coté, Guillaume; Moore, Jean-Sébastien; Ghaedrahmati, NabiAllah; Abdoli, Asghar; Bernatchez, Louis (Scientific reports, 2018)
Two blind Iran cave barbs, Garra typhlops and Garra lorestanensis , exist in sympatry in a single subterranean habitat, raising the hypothesis that they may represent a case of sympatric speciation following a colonization event. Their different mental disc forms have prompted some authors to propose the alternative hypothesis of two separate colonization events. In this study, we analysed a genome-wide panel of 11,257 SNPs genotyped by means of genotyping-by-sequencing combined with mitochondrial cytochrome c oxidase sub-unit I sequence data, field observations and morphological traits to test these two hypotheses. Field data suggest some degree of ecological divergence despite some possible niche overlap such that hybridization is possible. According to both nuclear and mtDNA data, the cave barb species are monophyletic with close phylogenetic relationships with Garra gymnothorax from the Karun-Dez and Karkheh river basins. The historical demography analysis revealed that a model of Isolation-with-Migration (IM) best fitted the data, therefore better supporting a scenario of sympatric origin than that of allopatric isolation followed by secondary contact. Overall, our results offer stronger support to the hypothesis that speciation in the subterranean habitat could have occurred in sympatry following a colonization event from the Karun-Dez-Karkheh basins in the Zagros Mountains of Iran.